1999
DOI: 10.2307/2657193
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Plant Species Invade Hot Spots of Native Plant Diversity

Abstract: Some theories and experimental studies suggest that areas of low plant species richness may be invaded more easily than areas of high plant species richness. We gathered nested-scale vegetation data on plant species richness, foliar cover, and frequency from 200 1-m 2 subplots (20 1000-m 2 modified-Whittaker plots) in the Colorado Rockies (USA), and 160 1-m 2 subplots (16 1000-m 2 plots) in the Central Grasslands in Colorado, Wyoming, South Dakota, and Minnesota (USA) to test the generality of this paradigm.At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
635
9
6

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(724 citation statements)
references
References 46 publications
71
635
9
6
Order By: Relevance
“…Thus, increases in richness have mainly occurred in communities that are (or were) still on the rising part of the unimodal biodiversity-fertility/disturbance curves or, more locally, where reduced land-use intensity impacted communities on the left of the mode. Our results therefore lead to the further prediction that initial abiotic conditions help control the extent to which species with losing and winning trait syndromes can coexist, albeit temporarily, and hence whether a-diversity initially increases or decreases in response to the same human-induced driving forces (Stohlgren et al 1999;Wright & Jones 2004). Dependence upon starting conditions is therefore a further obvious reason why a consistent relationship between species diversity changes and biotic homogenization is unlikely.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, increases in richness have mainly occurred in communities that are (or were) still on the rising part of the unimodal biodiversity-fertility/disturbance curves or, more locally, where reduced land-use intensity impacted communities on the left of the mode. Our results therefore lead to the further prediction that initial abiotic conditions help control the extent to which species with losing and winning trait syndromes can coexist, albeit temporarily, and hence whether a-diversity initially increases or decreases in response to the same human-induced driving forces (Stohlgren et al 1999;Wright & Jones 2004). Dependence upon starting conditions is therefore a further obvious reason why a consistent relationship between species diversity changes and biotic homogenization is unlikely.…”
Section: Discussionmentioning
confidence: 57%
“…Experimental studies conducted at small scales tend to fi nd support for DIH, largely through limiting similarity mechanisms, but observational studies tend to fi nd the opposite pattern (Fridley et al 2007 ). Many researchers have suggested that such confl icting patterns indicate that the role of diversity itself in invasibility is weak compared to other factors like propagule pressure (Brown & Peet 2003 ), variation in resource availability (Stohlgren et al 1999(Stohlgren et al , 2003 or disturbance levels (Byers & Noonburg 2003 ; see also Shea & Chesson 2002 ;Huston 2004 ;Tilman 2004 ;Fridley et al 2007 ;Davis 2009 ). The view, referred to as niche -driven community assembly (Hubbell 2001 ) or species packing (Slobodkin 2001 ), asserts that patterns of biodiversity, such as species richness, are determined by differences between species in how effectively they acquire particular resources in an environment where the quality of one or more resources varies (e.g.…”
Section: From Elton To Macarthur: An Invasion Framework Built On Limimentioning
confidence: 99%
“…For instance, Lyons and Schwartz (2001) concluded that the removal of rare native plant species was more likely to facilitate the invasion of the exotic grass, Lolium temulentum, in comparison with areas that sustained higher levels of diversity. However, other research has provided mixed support for this hypothesis (Robinson et al, 1995), with one study concluding that highly diverse communities are fundamentally unstable, resulting in a regular turnover of species (Stohlgren et al, 1999).…”
Section: Introductionmentioning
confidence: 99%